Non-Genetic Risk Factors for The Formation of Factor VIII Inhibitors in Hemophilia A Patients in RSUD Dr. Soetomo - Intani Dewi Syahti Fauzi; Maria C Shanty Larasati; I Dewa Gede Ugrasena (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2019)
Neutralizing alloantibodies (inhibitors) is one of the complications that affect the morbidity and quality of life of hemophilia patient and can be caused by multifactorials. Genetic and inhibitors examination are not routine and expensive. Therefore, identification of non-genetic factors is important to predict the formation of inhibitors. To analyze non-genetic risk factors for the formation of factor VIII inhibitors in children with Hemophilia A.  A cross-sectional study of hemophilia children aged 1-18 years at the pediatric hematology oncology outpatient clinic of Dr. Soetomo hospital in March-April 2018. Factors analyzed included the severity of hemophilia, early age of diagnosis, initial age of therapy, type of replacement therapy, frequency of factor VIII administration, and severity of bleeding by bleeding score. Statistical analysis using Chi square, Fisher, ANOVA and logistic regression analysis. A total of 29 children were evaluated, 7/29 mild, 15/29  moderate, and 7/29  severe hemophilia. Inhibitors were found in 11/29 subjects, 7/11 low (1-5 BU) and 4/11 high titer (> 5 BU). The initial age of diagnosis â‰¤ 1 year is associated with the formation of factor VIII inhibitors (OR 8.75; 95% CI = 1.5-50.2; p = 0.015). Severity of hemophilia, early age of therapy, type of replacement therapy, frequency of therapy, and bleeding score was not significantly associated with the formation of factor VIII inhibitors. The initial age of diagnosis less than 1 year is a significant risk factor for the formation of factor VIII inhibitors.